Prevalence of Abnormal Patellofemoral Congruence in Elite American Football Players and Association with Quadriceps Isokinetic Testing - Brown, Christopher A.; Carragee, Cat; Sox-Harris, Alex; Merchant, Alan C.; Mcadams, Timothy R. (The Journal of Knee Surgery, 2014)
Abnormal patellofemoral joint alignment has been discussed as a potential risk factor for patellofemoral disorders and can impact the longevity of any elite athlete's career. The prevalence of abnormal patellofemoral congruence in elite American football athletes is similar to the general population and does not have a relationship with quadriceps isokinetic testing. A total of 125 athletes (220 knees) from the 2011 National Football League (NFL) Combine database who had radiographic and isokinetic studies were reviewed. Congruence angles (CA) and lateral patellofemoral angles (LPA) were calculated on a Merchant radiographic view. Isokinetic testing was used to determine quadriceps-to-hamstring strength (Q/H) ratio and side-to-side deficits. The relationships between abnormal CA and LPA with Q/H ratios, side-to-side deficits, and body mass index (BMI) were examined in separate logistic regression models. A Chi-square test was used to examine the association between CA and player position. Of all, 26.8% of the knees (95% CI: 21.1–33.2%) had an abnormal CA. Knees with normal CA (n = 161) did not significantly differ from those with an abnormal CA (n = 59) in Q/H ratios (mean: 0.699 vs. 0.728, p = 0.19) or side-to-side quadriceps deficits (mean: 4.0 vs. 1.24, p = 0.45). For each point increase in BMI, the odds ratio (OR) of abnormal congruence increased by 11.4% (p = 0.002). Of all the knees, 4.1% (95% CI: 1.9–7.6%) had an abnormal LPA, and this was not associated with Q/H ratios (p = 0.13). For each point increase in BMI, the odds of abnormal LPA increased by 16% (p = 0.036). CA abnormality had much higher odds of having an abnormal LPA (OR: 5.96, p = 0.014). We found that abnormal patellofemoral radiographic alignment in elite American football players is relatively common and there was no association with isokinetic testing.
Keywords: abnormal patellofemoral congruence; malalignment; athlete; NFL